A Cost‐Effective Iron Based Covalent Organic Framework and Its Composite Electrocatalyst for Active and Stable Oxygen Reduction Reaction in Alkaline Solution. Issue 23 (5th November 2021) - Liu, Muye; Wen, Yue; Lu, Luhua; Kang, Qi; Xie, Zhicheng; Chen, Ying; Tian, Xiaocong; Jin, Hongyun; Liu, Jinghai
Abstract: Earth‐abundant non‐precious‐metal‐based materials are promising candidates for low‐cost oxygen reduction reaction (ORR) catalysts. Within those elements, iron is the cheapest given the abundant resources. However, there are few iron‐based ORR catalysts given the difficulty of achieving good electrocatalytic activity and stability with them in comparison to cobalt‐ and nickel‐based catalysts. Moreover, the synthesis of iron‐based ORR catalysts is energy intense and normally requires complicated processes. This work reports an iron‐based covalent organic framework (COF) synthesized through a one‐step low‐temperature solid reaction, which is cost effective and energy saving. The iron‐based COF, named IPPc, shows a high four‐electron‐transfer reaction selectivity. After compositing it with reduced graphene oxide, the resulting composite preserves the high electron‐transfer reaction selectivity and displays a largely enhanced activity and stability. Abstract : Active catalysts : Iron polyphthalocyanine (IPPc) has been successfully synthesized by using a low‐temperature solid‐state method. The Fe−N active center in the structure of IPPc can effectively reduce O2 to OH − through a four‐electron transfer pathway. After compositing it with reduced graphene oxide, both the activity and selectivity of IPPc are promoted, owing to enhancement of the specific capacity and improved stability.